2015
DOI: 10.1111/jcpp.12463
|View full text |Cite
|
Sign up to set email alerts
|

Extending the ‘cross‐disorder’ relevance of executive functions to dimensional neuropsychiatric traits in youth

Abstract: Background Evidence that different neuropsychiatric conditions share genetic liability has increased interest in phenotypes with ‘cross-disorder’ relevance, as they may contribute to revised models of psychopathology. Cognition is a promising construct for study; yet, evidence that the same cognitive functions are impaired across different forms of psychopathology comes primarily from separate studies of individual categorical diagnoses versus controls. Given growing support for dimensional models that cut acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…The proposed model displayed differential validity in terms of executive function since we found a different profile for dimensions within the same broad spectrum. The proposed model confirmed previous findings of the association between worse executive function and the general psychopathology factor in youth [73], [55], [74], [75], [18] and the association between inattention-hyperactivity and worse executive function [11], [76], [77]. The bifactor model displayed an EF divergent profile for anxiety dimensions; worse performance related to fear and better performance related to distressful thoughts.…”
Section: Discussionsupporting
confidence: 85%
“…The proposed model displayed differential validity in terms of executive function since we found a different profile for dimensions within the same broad spectrum. The proposed model confirmed previous findings of the association between worse executive function and the general psychopathology factor in youth [73], [55], [74], [75], [18] and the association between inattention-hyperactivity and worse executive function [11], [76], [77]. The bifactor model displayed an EF divergent profile for anxiety dimensions; worse performance related to fear and better performance related to distressful thoughts.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, there also appears to be an underlying shared mechanism or ability that contributes to performance across different EF tasks lending support to the unity of the EF construct (Duncan et al, 1997; Hanes et al, 1996; Miyake et al, 2000; Salthouse et al, 2003) (McGrath et al, 2015). The unity and diversity of EF processes provides the opportunity to examine EF from a holistic perspective, with a focus on the combined measurement of EF, as well as from a component perspective.…”
Section: Executive Functioningmentioning
confidence: 96%
“…We found four latent factors: verbal memory, verbal fluency, visual-spatial processing, and common executive (CE). Similar to previous research (McGrath et al, 2016), CE was created as a broad factor reflecting inhibition, switching, and processing speed because we did not find support for distinction among these constructs in our analysis.…”
Section: Methodsmentioning
confidence: 95%
“…Previous research indicates that g and P are correlated (Caspi et al, 2014), and variance in P can be partially accounted for by cognitive skills. For example, McGrath and colleagues (2016) demonstrated that shared variance among psychosis, mania, and autistic traits was partially explained by a common executive cognition factor. This model is consistent with a cognitive endophenotype model and indicates that measures of cognition are more closely tied to brain functions that give rise to the abnormal psychiatric phenotype.…”
Section: Comorbid Inattention In Autism Spectrum Disordermentioning
confidence: 99%